Closed intensive care units and sepsis patient outcomes: a secondary analysis of data from a multicenter prospective observational study in South Korea - Kyeongman Jeon; Jin Hyoung Kim; Kyung Chan Kim; Heung Bum Lee; Hongyeul Lee; Song I Lee; Jin-Won Huh; Won Gun Kwack; Youjin Chang; Yun-Seong Kang; Won Yeon Lee; Je Hyeong Kim; et al. (Acute and Critical Care)
Background Sepsis is a leading cause of intensive care unit (ICU) admission. However, few studies have evaluated how the ICU model affects the outcomes of patients with sepsis. Methods This post hoc analysis of data from the Management of Severe Sepsis in Asia’s Intensive Care Units II study included 537 patients with sepsis admitted to 27 ICUs in Korea. The outcome measures of interest were compared between the closed ICU group, patients admitted under the full responsibility of an intensivist as the primary attending physician, and the open ICU group. The association between a closed ICU and ICU mortality was evaluated using a logistic regression analysis. Results Altogether, 363 and 174 enrolled patients were treated in open and closed ICUs, respectively. Compliance with the sepsis bundles did not differ between the two groups; however, the closed ICU group had a higher rate of renal replacement therapy and shorter duration of ventilator support. The closed ICU group also had a lower ICU mortality rate than the open ICU group (24.7% vs. 33.1%). In a logistic regression analysis, management in the closed ICU was significantly associated with a decreased ICU mortality rate even after adjusting for potential confounding factors (adjusted odds ratio, 0.576; 95% CI, 0.342–0.970), and that association was observed for up to 90 days. Conclusions Sepsis management in closed ICUs was significantly associated with improved ICU survival and decreased length of ICU stay, even though the compliance rates for the sepsis bundles did not differ between open and closed ICUs.